2017
DOI: 10.5194/acp-17-11727-2017
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reactions of mineral dust aerosol: implications for tropospheric oxidation capacity

Abstract: Abstract. Heterogeneous reactions of mineral dust aerosol with trace gases in the atmosphere could directly and indirectly affect tropospheric oxidation capacity, in addition to aerosol composition and physicochemical properties. In this article we provide a comprehensive and critical review of laboratory studies of heterogeneous uptake of OH, NO 3 , O 3 , and their directly related species as well (including HO 2 , H 2 O 2 , HCHO, HONO, and N 2 O 5 ) by mineral dust particles. The atmospheric importance of he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 378 publications
(657 reference statements)
3
124
0
Order By: Relevance
“…Aerosol liquid water (or surface‐adsorbed water) largely determines kinetics, mechanisms, and products of heterogeneous reactions (Rubasinghege & Grassian, ; Tang et al, ; Wu et al, ). Mitroo et al () found that at a given RH, N 2 O 5 uptake coefficients decreased whereas ClNO 2 production yield increased with soluble ion fractions in saline mineral dust samples.…”
Section: Resultsmentioning
confidence: 99%
“…Aerosol liquid water (or surface‐adsorbed water) largely determines kinetics, mechanisms, and products of heterogeneous reactions (Rubasinghege & Grassian, ; Tang et al, ; Wu et al, ). Mitroo et al () found that at a given RH, N 2 O 5 uptake coefficients decreased whereas ClNO 2 production yield increased with soluble ion fractions in saline mineral dust samples.…”
Section: Resultsmentioning
confidence: 99%
“…The latter treatment is suitable when ambient concentrations are low and the air mass is relatively stable, but it may be problematic in polluted environments with high fresh NO x emissions, high O 3 concentrations, and rapidly changing air mass. Several recent studies have revealed active N 2 O 5 heterogeneous processes on aerosols at polluted sites and its significant impacts on photochemistry and secondary aerosol formation due to abundant NO x , O 3 , and aerosols (e.g., Li et al, 2016;Tham et al, 2016;Wang et al, 2016;Yun et al, 2018). The γ N 2 O 5 derived from ambient concentration measurements showed different characteristics and dependence compared to previous measurements in relatively clean environments (Morgan et al, 2015;.…”
Section: Introductionmentioning
confidence: 83%
“…In this study, as shown in Figure g, Oxalate/Ca + showed a three‐spike diurnal pattern peaking at 3:00, 5:00, and 17:00. The aqueous oxidation of glyoxal by OH, H 2 O 2 , and other peroxides could drive the nighttime elevation of oxalate in the dust droplets (Tang et al, ). The nighttime peak of oxalate has been observed by Sullivan and Prather (), but they proposed that the peak was majorly caused by long‐range transport.…”
Section: Resultsmentioning
confidence: 99%